Thoracic Aortic Three-Dimensional Geometry - Cameron Beeche; Marie-Joe Dib; Bingxin Zhao; Joe David Azzo; Hamed Tavolinejad; Hannah Maynard; Jeffrey Thomas Duda; James Gee; Oday Salman; Walter R. Witschey; Julio Chirinos (Pulse)
Introduction: Aortic structure impacts cardiovascular health through multiple mechanisms. Aortic structural degeneration occurs with aging, increasing left ventricular afterload and promoting increased arterial pulsatility and target organ damage. Despite the impact of aortic structure on cardiovascular health, three-dimensional (3D) aortic geometry has not been comprehensively characterized in large populations. Methods: We segmented the complete thoracic aorta using a deep learning architecture and used morphological image operations to extract multiple aortic geometric phenotypes (AGPs, including diameter, length, curvature, and tortuosity) across various subsegments of the thoracic aorta. We deployed our segmentation approach on imaging scans from 54,241 participants in the UK Biobank and 8,456 participants in the Penn Medicine Biobank. Conclusion: Our method provides a fully automated approach toward quantifying the three-dimensional structural parameters of the aorta. This approach expands the available phenotypes in two large representative biobanks and will allow large-scale studies to elucidate the biology and clinical consequences of aortic degeneration related to aging and disease states.